CONTROLE QUÍMICO EM PÓS-EMERGÊNCIA DE ESPÉCIES DE BRACHIARIA EM TRÊS ESTÁDIOS VEGETATIVOS - Marques, R.p. [UNESP]; Rodella, R.a. [UNESP]; Martins, M. [UNESP] (Instituto Biológico, 2020)
The aim of this study was to correlate the chemical control efficacy in post-emergence of Brachiaria decumbens Stapf. (signal grass) and Brachiaria plantaginea Hitchc. (alexandergrass) through ACCase-inhibitor enzyme herbicide application in function of the stage of development of the plant in order to contribute to the chemical management of these weed species. B. decumbens and B. plantaginea were sown in plastic pots filled with soil and kept in a greenhouse. For chemical control evaluation, the following herbicides were tested (g ha-1): fluazifop-p-butyl at 150, haloxyfop-methyl at 50, and sethoxydim at 230. The herbicides were applied in all three plant development phases: stage 1 (plants presenting 4-6 leaves at 15 days after emergence), stage 2 (plants presenting 3-4 tillers at 23 days after emergence), and stage 3 (adult plants in the beginning of flowering at 48 days after emergence). Evaluations were done at 4, 7, 10, 14, 17, 21, 24, and 28 days after herbicide application. The developmental stage of the two Brachiaria species was instrumental in the efficiency of the control provided by different herbicides. Sethoxydim was the most efficient herbicide in controlling Brachiaria species in the three evaluated development stages.

O objetivo do presente trabalho foi relacionar a eficiência do controle químico em pós-emergência de Brachiaria decumbens Stapf. (capim-braquiária) e Brachiaria plantaginea Hitchc. (capim-marmelada) por meio de herbicidas inibidores da enzima ACCase em função do estádio de desenvolvimento da planta, visando fornecer subsídios para o manejo químico dessas espécies daninhas. A semeadura de B. decumbens e B. plantaginea foi feita em vasos plásticos contendo solo e mantidos em casa de vegetação. Para a avaliação do controle químico foram testados os herbicidas (g ha-1): fluazifop-p-butil a 150, haloxyfop-methyl a 50e sethoxydim a 230. Os herbicidas foram aplicados em três estádios de desenvolvimento da planta: estádio 1 (plantas com 4-6 folhas aos 15 dias após a emergência), estádio 2 (plantas com 3-4 perfilhos aos 23 dias após a emergência) e estádio 3 (plantas adultas no início do florescimento aos 48 dias após a emergência). As avaliações de controle foram feitas 4, 7, 10, 14, 17, 21, 24 e 28 dias após a aplicação dos herbicidas. O estádio de desenvolvimento das duas espécies de Brachiaria foi determinante na eficiência de controle proporcionado pelos diferentes herbicidas estudados. Verificou-se que o herbicida sethoxydim foi mais eficiente no controle das espécies de Brachiaria, nos três estádios de desenvolvimento estudados.
CHEMICAL CONTROL IN POST-EMERGENCE OF SPECIES OF BRACHIARIA IN THREE VEGETATIVE STAGES
Keywords: ACCase inhibitors; Alexandergrass; grasses; signal grass; Capim-braquiária; capim-marmelada; gramíneas; inibidores da ACCase